2017
DOI: 10.19044/esj.2017.v13n34p211
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Employer-Based Brand Equity and Employer Brand Pyramid

Abstract: Employer branding is referred to as a firm's efforts to promote, both within and outside the firm, a clear view of what makes it different and desirable as an employer. It constitutes an important concept in today's knowledge intensive contexts where attracting employees with superior skills and knowledge comprises a primary source of competitive advantage. This research paper will focus on building employer brand equity by exploring the previous research on employer brand. Based on the Keller brand pyramid th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Ambler and Barrow (1996) defined EB as “the package of functional, economic and psychological benefits provided by employment, and identified with the employing company”. (Lievens et al , 2007) stated that “employer branding is a specific form of managing corporate identities by creating both within and outside the firm an image of the firm as a distinct and desirable employer.” Kashive and Khanna (2017a, 2017b) based on the Keller brand pyramid built EB pyramid and saw if the same concepts of customer-based brand equity can be used to conceptualize the idea of employer-based brand equity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambler and Barrow (1996) defined EB as “the package of functional, economic and psychological benefits provided by employment, and identified with the employing company”. (Lievens et al , 2007) stated that “employer branding is a specific form of managing corporate identities by creating both within and outside the firm an image of the firm as a distinct and desirable employer.” Kashive and Khanna (2017a, 2017b) based on the Keller brand pyramid built EB pyramid and saw if the same concepts of customer-based brand equity can be used to conceptualize the idea of employer-based brand equity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kashive and Khanna (2017a, 2017b) showed that advertisement, publicity and word of mouth of early recruitment activities impact all aspects of employer brand knowledge, such as employer familiarity, employer image and employer reputation. Employer reputation and employer image impacted organization attractiveness, whereas employer familiarity and employer image impacted firm performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus an employer brand is an effective tool for attracting, selecting, and retaining superior employees. Based on Keller's customer-based brand equity model, Kashive & Khanna, (2017) conceptualized the idea of employer-based brand equity. The employerbased brand equity model suggests that by creating a desirable and favorable company image in employees' minds, employees would prefer a certain company.…”
Section: Hr Branding Versus Marketing Brandingmentioning
confidence: 99%
“…Companies with strong employer identity will be perceived as more attractive compared to others. Employee identification with the company has great importance, because employees' attitudes and behaviors could reinforce or weaken the corporate brand (Kashive & Khanna, 2017). Strong brand meanings should provide a favorable response from an employee when selecting a certain company for which to work.…”
Section: Hr Branding Versus Marketing Brandingmentioning
confidence: 99%
“…For example, values that attract employees and/or are conducive to their maintenance were analysed by S.D.S. Tikson, N. Hamid and R. Mardiana Kashive and V. T. Khanna (2017). However, all these surveys were conducted only for employers who are companies.…”
Section: Introductionmentioning
confidence: 99%